ACADEMIC PROCRASTINATION AT UNIVERSITY STUDENTS: A SYSTEMATIC LITERATURE REVIEW - LUBIS, AMINAH; HASIBUAN, AHMAD SOLEH (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
Research on academic procrastination in college students has grown very rapidly in recent years. This journal aims to review: (a) the definition of academic procrastination, and (b) the measurement of academic procrastination in students. This journal review will involve journals published in the years 2011-2020. The conclusions of this literature review are (a) the definitions that are often used to explain academic procrastination among students and explain about dimension of acadenic procrastination, and (b) review the measurement of academic procrastination used during the past 10 years among students. These findings can provide recommendations for measuring academic procrastination and evaluation for tertiary institutions at the undergraduate or postgraduate program level.